Prediction models for clinical outcome after a carotid revascularization procedure: an external validation study - Volkers, EJ; Algra, A; Kappelle, LJ; Roubin, GS; Jansen, O; Howard, G; Hendrikse, J; Halliday, AW; Gregson, J; Fraedrich, G; Eckstein, H-H; Calvet, D; et al. (American Heart Association, 2018)
Background and Purpose Prediction models may help physicians to stratify patients with high and low risk for periprocedural complications or long-term stroke risk after carotid artery stenting (CAS) or carotid endarterectomy (CEA). We aimed to evaluate external performance of previously published prediction models for short- and long-term outcome after carotid revascularization in patients with symptomatic carotid artery stenosis. Methods From a systematic review, we selected all prediction models that used only readily available patient characteristics known before procedure initiation. Follow-up data from 2,184 CAS and 2,261 CEA patients from four randomized trials (EVA-3S, SPACE, ICSS, and CREST) were used to validate 23 short-term outcome models to estimate stroke or death risk ≤30 days after the procedure and the original outcome measure for which the model was developed. Additionally, we validated seven long-term outcome models for the original outcome measure. Predictive performance of the models was assessed with c-statistics and calibration plots. Results Stroke or death ≤30 days after the procedure occurred in 158 (7.2%) patients after CAS and in 84 (3.7%) patients after CEA. Most models for short-term outcome after CAS (n=4) or CEA (n=19) had poor discriminative performance (c-statistics ranging from 0.49 to 0.64) and poor calibration with small absolute risk differences between the lowest and highest risk groups and overestimation of risk in the highest risk groups. Long-term outcome models (n=7) had slightly better performance with c-statistics ranging from 0.59 to 0.67 and reasonable calibration. Conclusions Current models did not reliably predict outcome after carotid revascularization in a trial population of patients with symptomatic carotid stenosis. In particular, prediction of short-term outcome appeared to be difficult. Further external validation of existing prediction models or development of new prediction models is needed before such models can be used to support treatment decisions in individual patients.